1990
DOI: 10.1080/00288233.1990.10428422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cobalt application on the cobalt status of pastures 1. Pastures with history of regular cobalt application

Abstract: Pasture and soil cobalt (Co) concentrations weremonitored for 8-9 yearson six properties that had been developed in pasture for periods ranging from 15 to 24 years on yellowbrown pumice soils in the Rotorua-Taupo area, NewZealand Allsiteshadbeentopdressedannually withCo beforethe survey beganin 1979, but from then the amount and frequency of Co applied was reducedconsiderably.Despitethisreduction, pasture Co concentration remained adequate for grazing livestock and soil Co extracted with EDTA was maintained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In fact, plant Co concentrations are typically <10 mg/kg and, more often than not, <1 mg/kg (Adams and Honeysett 1964;Adams et al 1969;Gille and Graham 1971;Gupta 1993;Klessa et al 1989;Li et al 2004;McLaren et al 1987;McLaren and Williams 1981;Nicolls and Honeysett 1964;Paterson et al 1991;Price et al 1955;Rosbrook et al 1992;Sherrell et al 1990). For comparative purposes, the threshold deficiency concentration of Co in pastures for sheep and cattle grazing has been identified as 0.05-0.1 mg/kg (Gupta 1993;Klessa et al 1989;Sherrell 1990b;Sherrell et al 1990). Despite the fact that higher plants may control, to a large degree, Co uptake, soil parameters are also likely to be involved in the seven orders of magnitude difference in plant Co concentrations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In fact, plant Co concentrations are typically <10 mg/kg and, more often than not, <1 mg/kg (Adams and Honeysett 1964;Adams et al 1969;Gille and Graham 1971;Gupta 1993;Klessa et al 1989;Li et al 2004;McLaren et al 1987;McLaren and Williams 1981;Nicolls and Honeysett 1964;Paterson et al 1991;Price et al 1955;Rosbrook et al 1992;Sherrell et al 1990). For comparative purposes, the threshold deficiency concentration of Co in pastures for sheep and cattle grazing has been identified as 0.05-0.1 mg/kg (Gupta 1993;Klessa et al 1989;Sherrell 1990b;Sherrell et al 1990). Despite the fact that higher plants may control, to a large degree, Co uptake, soil parameters are also likely to be involved in the seven orders of magnitude difference in plant Co concentrations.…”
Section: Introductionmentioning
confidence: 94%
“…Despite this knowledge, Co deficiency was still a common nutritional disorder of ruminants in the UK in the 1980s and, at that time, constituted 15-20% of all recorded trace element deficiencies in farm animals (Klessa et al 1989). In severe cases, Co deficiency in ruminants can be fatal (Klessa et al 1989) and, in the scientific literature, has been reported to occur in Scotland (Klessa et al 1989), Australia (Nicolls and Honeysett 1964) and New Zealand (Sherrell et al 1990). Typically, pasture top dressing with Co salts or the oral administration of Co have been used to alleviate Co deficiency in ruminants (Smith 1990).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A 10-year study by Sherrell et al (1990) found that lucerne grown on pumice soil had a long-term average Co content only half that of white clover. However, there is evidence that other deep-rooting plants have higher levels of trace elements than ryegrass and white clover {Trifolium repens).…”
Section: Scenariomentioning
confidence: 99%
“…After several year's application, pasture Co concentrations can be maintained at adequate levels for grazing animals (Sherrell 1990a). However, initial applications of CoSO4 to a deficient site result in immediate elevation of herbage Co concentration followed by a rapid decline within a few months (Sherrell 1990b).…”
Section: Introductionmentioning
confidence: 99%